GAMYBOS ĮMONĖS ATSARGŲ APSKAITOS TYRIMAS = INVENTORY ACCOUNTING RESEARCH OF MANUFACTURING COMPANY - Liucija Budrienė; Audronė Meškelienė; Janina Vaitiekienė (Taikomieji tyrimai studijose ir praktikoje, 2018)
Each company, as a profit-making entity, has the main objective of maximizing profits. The company's purpose is greatly influenced by its available current assets. In the manufacturing company, the largest part of current assets consists of stock, therefore, it is very important to properly organize their accounting. Inventories play the most important role for sales costs and partly in work result. The aim of the research was to analyze reserve the methodology of inventory accounting of a production company and submit proposals for its improvement. The methods of analysis and synthesis of legislation and scientific literature are used to justify the methods of accounting for inventory classification, valuation, pricing and consumption. The study uses enterprise data systematization, analysis and generalization methods to determine how the inventory accounting methodology complies with business accounting standards. Production cost of inventories includes the production-related direct and indirect production costs. Direct costs are costs that are directly related to the subject of a specific item, and indirect costs are not possible or difficult to assign to a specific item of expenditure. Calculating the cost of consumed and sold inventories, companies may apply one of three inventory pricing methods - FIFO, weighted average, and specific pricecing. With the inventory price fluctuating, each chosen pricing method can give a very different result. Different reserve pricing methods have a significant impact on the gross profit margin and taxes. Use of inventories or sales in accounting can be recorded continuously or periodically. Continuous reserve accounting method is more expensive, but rmore efficient information is available to manage inventory. The researchers has provided recommendations for the improvement of inventory accounting for the company. The company only includes the expenses of salaries and raw materials (direct production costs) into the costs of production of items. However, the cost of the products, obtained in this way, is not accurate. Therefore, it is recommended to include indirect production costs (disposable items, low-value assets, additional materials, water, electricity, gas, purchased services, depreciation of production facilities and equipment) for distributed product types. The criteria for allocating indirect costs must reflect, as fairly as possible, the relationship between the distribution of costs and the production and sales of products for which these costs are allocated. Therefore, various criteria for the allocation of indirect costs (costs of basic raw materials, costs of wages and salaries of key production workers, number of key production staff, direct production costs, etc.) are suggested for the different types of expenses. The improvement of inventory accounting of the company enables to more accurately determine the cost of inventories, to make a more precise estimate of the cost of production, and to justify the sale price of inventories. Taking into account the results of the research, it is possible to optimize not only the cost but also the sales revenue.